CORPORATE GOVERNANCE STRATEGIC PERFORMANCE AS A SIGNIFICANT STRATEGIC MANAGEMENT TO PROMOTING PROFITABILITY: A STUDY IN UAE - Alabdullah, Tariq Tawfeeq Yousif; Naseer, Howraa Qaseem (Transpublika Publisher, 2023)
The aim of this study is to objectively investigate how board size, firm size, and firm age impact the financial performance of organizations listed in Dubai. A quantitative technique was employed using a sample of 40 non-financial firms listed on the Dubai Stock Exchange for the fiscal year 2022. This selected group of businesses is expected to provide valuable data to achieve the study's objectives and address the relevant research questions. The results of the research shed light on the relationship between the variables of interest through data analysis and statistical testing. It was found that the size of the board has minimal to no influence on the financial performance of the sampled companies. However, the study revealed a significant and positive correlation between company age and size and firm performance, as measured by ROA. It suggests that as businesses develop over time and increase in size, they tend to demonstrate higher levels of profitability. These findings emphasize the importance of considering factors other than board size when examining the connection between corporate governance characteristics and firm performance. Other organizational attributes, such as age and size, exert a more substantial influence on financial performance, even if board size may not be a significant driver. Within the context of Dubai-listed companies, these findings provide valuable insights into the nature of corporate governance and its impact on firm performance. The results of this study underscore the need for a comprehensive understanding of corporate governance processes and their effects on financial outcomes.